The Disruption of Labor Law in the Platform Economy: Towards a Normative Reconfiguration - Hermanto, Hermanto; Hendriks, Pieter; Vermeer, Sophie (Rechtsnormen: Journal of Law, 2025)
Background. The emergence of the platform economy—characterized by gig work, algorithmic management, and digital intermediation—has profoundly challenged traditional labor law frameworks. Conventional legal categories such as “employee” and “employer” often fail to capture the complexity of work relationships within platform-based environments. As a result, workers engaged in ride-sharing, food delivery, and other digital services are frequently excluded from fundamental labor protections, including minimum wage, social security, and collective bargaining rights. Purpose. This study aims to critically examine how platform-mediated work disrupts existing labor law norms and to propose a normative reconfiguration that reflects the evolving nature of work. Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. The findings reveal widespread legal fragmentation, insufficient protection for platform workers, and a growing tension between labor flexibility and social security. Conclusion. The study concludes that a redefinition of labor status and regulatory categories is essential for restoring legal coherence and ensuring just working conditions in the platform economy. A hybrid regulatory model integrating digital rights with labor standards is proposed as a pathway forward.